Avaliação pedagógica e deficiência intelectual : formação de profissionais da rede pública - Stelmachuk, Anaí Cristina da Luz (2017)
The present research had as an objective to identify the concepts multifunctional-resource-class teachers and school supervisors have of intellectual disability and evaluation, after being submitted to an education course. It also aimed at analyzing how the assessment processes of students showing possible intellectual disability for enrollment in special education programs have been occurring, and subsidize work in a pedagogical evaluation which guarantees each and every student the right to learn in school. Developed in a town in Parana State which adopts the psycho-educational evaluation in the school context, a model constituted of pedagogical assessment aided by psychological opinion with the diagnoses of the disability, its subjects were the multifunctional-resource-class teachers and school supervisors of the public municipal education network, the ones in charge of the pedagogical assessment and the Coordinator of Basic Education of Secretaria da Educação Municipal ( Municipal Board of Education). Supported by critical educational theories and their bases, the methodological forwarding happened under a historic and dialectic perspective, whose approach makes possible the proximity and understanding of social practices which involve the processes studied, in order to more than understand them, to try to transform them. The course offered to the participants in the research was based in the historic-critic pedagogy and the educational meetings were videotaped for data collection. The talks were transcribed and organized in theme axes about: the education course, concepts of evaluation, concepts of intellectual disability and evaluation practices. As a result, it was verified that the participants’ concepts of evaluation validate this tool as a means to indicate ways towards the student’s learning. Nevertheless, the course takers focus more on the skills that must be developed by the students than on the factors external to them, which make this development possible, such as the very pedagogical practice itself. Concerning the concept of intellectual disability, it was noticed a mixture of concepts: some course takers present a speech primarily focused on an organicist view, and others, more focused on the interaction perspective. About the evaluation practice, it was verified that the course takers have knowledge about the necessary proceedings to refer the students to assessment and the norms adopted by the city; some course takers showed resistance to the participation of school professionals in the evaluation process, indicate the segmentation among the teams who act within and outside the school, besides the predominance of the opinions of such teams over the ones of the school pedagogical team. The clinical area professionals’ diagnoses are considered important, however criticism to them can be noticed, especially when their results do not correspond to the expectancy of the school. Based on the pedagogical evaluation performed in the school context, reports on students who had their learning process redefined and stopped being sent for psychological assessment in order to identify a possible disability outstands. It is concluded that the education course offered constituted a space for reflection, which made possible, changes in concepts of intellectual disability and its evaluation processes.